PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA PRA MENULIS MELALUI KARTU KATA KELAS 3 SD NEGERI BAJO - Anwar Marasabesy; Suhardi Abdullah; Santi M.J Wahid (PEDAGOGIK, 2022)
The research objectives consist of (1) Increasing prewriting activity through words card at 3rd gradeof SDNegeri Bajo and (2) Increasing students prewriting activities through word cards. There were22 students became the respondents of this reearch and this research used quantitative andqualitative approach with classroom action research (CAR)The result of this research showed that there was significant difference between 1st cycle and 2ndcycle showed up that there were positive and negatively reacting respond by the students. In usingword cards media showed that students were more enjoyable in learning process. Based on theresearch result of learning foundout that 7,1 % average. It is proved that card words media couldimproved students competence in learning prewriting in cycle one with categorize suficiently. Whilein the second cycle became 19 students passed attend their evaluation or 19 students of 20 students,thus the percentage reach 95 %. Based on the second cycle of the research, the researcher assumedthat the students prewriting competence through word cards increase at 3rd grade of SDNegeri Bajo